High density polyethilene tank as an alternative technique to ageing wine using wood staves - Loi, Francesco (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto